2019
DOI: 10.1136/bmj.l1579
|View full text |Cite
|
Sign up to set email alerts
|

Making nutrition guidelines fit for purpose

Abstract: Guidelines must ask the right questions and incorporate complexity to improve their relevance and quality, argue Lisa Bero and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…They found the reporting of results in such studies tended to be skewed in favor of the sponsoring industry, and that authors’ financial conflicts of interest were frequently undisclosed in journal publications. Such reporting bias and lack of transparency is especially problematic as it can lead to the development of inappropriate dietary guidelines [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found the reporting of results in such studies tended to be skewed in favor of the sponsoring industry, and that authors’ financial conflicts of interest were frequently undisclosed in journal publications. Such reporting bias and lack of transparency is especially problematic as it can lead to the development of inappropriate dietary guidelines [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the methodology for developing CPGs is well known and a variety of tools exist for guidelines development and appraisal, the present study showed that guidelines are not actually following the guidelines for CPG development . Many CPGs are falling short in selected AGREE domains, indicating that improvements are needed to increase guidelines’ transparency, fluency, and objectivity to ameliorate CPG adherence …”
Section: Discussionmentioning
confidence: 60%
“…Several recent studies have suggested that nutrition guidelines are not adequately adhering to the standards for CPG development . This is why a collective initiative to ameliorate nutrition guideline quality has been proposed, using novel tools such as the NutriRECS . Nutrition guidelines must adhere to international guideline standards (like the AGREE II); provide recommendations based on systematic review of existing evidence; suggest facilitators and monitoring and screening tools to ameliorate adherence and outcome; suggest recommendations formulated based on a holistic dietetic approach, like the Nutrition Care Process; provide clear, unambiguous recommendations concerning dietary manipulations and nutrient intakes; suggest sample menus or diet plans for each condition; disclose funding and conflicts of interest; and include dietitians and nutritionists in their development .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the 2014 WHO standards seem to lack adequate methods to evaluate evidence relevant to the shifts in nutrition priorities, such as food sustainability and food practice, including eating together and home cooking (18,19) . Because current evidence-based methods primarily rely on clinical trial findings (27) , we propose using approaches such as the logical maps to guide research questions in dietary guideline development. This may ensure evidence collection and evaluation are driven by the research questions rather than by the available methods, such as the hierarchy of evidence (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Because current evidence-based methods primarily rely on clinical trial findings (27) , we propose using approaches such as the logical maps to guide research questions in dietary guideline development. This may ensure evidence collection and evaluation are driven by the research questions rather than by the available methods, such as the hierarchy of evidence (27) . Therefore, future methods in developing dietary guidelines could consider allowing high-quality observational studies to address emerging food and nutrition priorities, which are not always suitable for randomised controlled trials.…”
Section: Discussionmentioning
confidence: 99%